Gama Tirtha Ideology in Ancient Myth of Ratu Gede Tengahing Sagara - Nurjaya Putra Mahardika, I Made; Cika, I Wayan; Sudewa, I Ketut (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl JulyDO - 10.24843/e-jl.2020.v14.i02.p05, 2020)
The Balinese can not be separated from their ancestral beliefs. The ancestral or idiological beliefs in Balinese society are conveyed through myths. One of the most well-known myths in Bali is the Ratu Gede myth. The myth of Ratu Gede is very trusted and believed in constructing worship rituals. The worship ritual that is routinely performed is the Nangluk Marana ritual. Nangluk Marana is a ritual handed down by the myth of Ratu Gede Nusa Penida. The myth of  Ratu Gede is not limited to the figure of Ratu Gede Nusa Penida, but in Bali it also found a similar myth called the myth of  Ratu Gede Tengahing Sagara. The name sagara which means the sea has shown its identity as the ruler of the ocean. The myth of Ratu Gede Tengahing Sagara as the ruler of the ocean is not only being told on the coast, but also spread out to the highlands. The idiological influence of Ratu Gede Tengahing Sagara's myth to the highlands cannot be separated from the intertwining of stories handed down from generation to generation. The intertwining that can be seen in the form of Ratu Gede Tengahing Sagara's sacred route is always related to water civilization.